2020
DOI: 10.1080/15397734.2020.1776131
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between the effects of shape memory alloys and carbon nanotubes on the thermal buckling of laminated composite beams

Abstract: One of the essentials for designing composite structures exposed to heat is the correct choice of reinforcing materials. In the present research work, a comparison is made between the performances of two well-known advanced materials, Shape Memory Alloys (SMAs) and Carbon Nanotubes (CNTs), in thermal bucking behavior of thin composite beams with simply supported boundary conditions. First, the effect of embedding SMA wires on the thermal buckling of laminated composite beams are examined. The stability equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Alongside, addition of these two materials as reinforcement has increased the thermal buckling performance. 54…”
Section: Finite Element Modelling Of Pfgmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside, addition of these two materials as reinforcement has increased the thermal buckling performance. 54…”
Section: Finite Element Modelling Of Pfgmsmentioning
confidence: 99%
“…Alongside, addition of these two materials as reinforcement has increased the thermal buckling performance. 54 In the above Figure 10, compressive loads on the four layered PFGM was applied along the thickness. The design of the PFGM involves various curing conditions with respect to the temperature they were cured instigated primarily.…”
Section: Finite Element Modelling Of Pfgmsmentioning
confidence: 99%
“…To increase the out-of-plane mechanical resistance of composite materials, the properties of both the matrix and fiber-matrix interface should be improved. Several authors [23][24][25][26][27] considered adding carbon nanoparticles to composite materials and concluded that this approach improves the properties of the fiber-matrix interface and toughness of the matrix. For instance, Boroujeni and Al-Haik 28 obtained a 20% and 50% increase in tensile strength and fatigue life of a carbon FRC with carbon nanotubes (CNTs) compared with the original material.…”
Section: Introductionmentioning
confidence: 99%
“…1 These materials, due to their more brittle nature than metal alloys, failures occur in their sublayers and in the form of matrix cracking, fiber breakage, the separation between fibers and matrix and etc. [2][3][4][5][6][7] Also, fiber-reinforced composites may actually be subject to different corrosion conditions. In such environments, the matrix shows a downward behavior due to loss of mechanical properties.…”
Section: Introductionmentioning
confidence: 99%